Estudo comparado da função testicular em diferentes linhagens de camundongos na maturidade sexual e ao longo do desenvolvimento pós-natal - Carolina Felipe Alves de Oliveira (2020)
Mice are important experimental models for studies involving reproductive aspects in mammals, mainly due to its low maintenance cost, high prolificacy, fast reproductive cycle, besides the possibility of genetic manipulation generating transgenic mice for specific objectives. Thus, strain comparative study provides background for the understanding of their testicular peculiarities, which enables their selection according to their own characteristics for applied experimental approaches in reproduction. Moreover, genetically mutated mice allow the study of specific gene functions in the testis. In this sense, our main goals in this thesis were to comparatively evaluate reproductive aspects in different mice strains along post-natal development and in sexual maturity (70 days). In the first paper, we evaluated, using morphometry, immunohistochemistry, hormone plasmatic levels and trypan blue injection, several reproductive parameters in three adult mice strains frequently used in the literature (C57BL6, Swiss and BALB/c). In this work we observed that the outbred Swiss strain was the one that presented most of the differences in comparison to the others, especially C57BL6. Furthermore, we quantified the testicular macrophages in each investigated strain and found a much higher proportion of these cells than the one so far described in the literature (between 0.63 and 1.26 Leydig cell/macrophage), reinforcing the importance of these cells in the testis. Interestingly, this macrophage proportion altered between the strains, indicating that genetic background impacts this parameter. Moreover, we identified that the testis from the different mice strains present distinct cell compositions, hormone levels and morphology, reinforcing the importance of the knowledge about the differences and peculiarities that each strain possesses in order to properly select and use them in studies involving specific parameters or treatments in reproduction. In the second paper, we investigated, through morphometry, immunohistochemistry and qPCR, Foxn1 and Prkdc genes functions in adult mice testis. Using mice strains that present mutation in these genes (nude and scid), we identified that Foxn1 transcription factor seem to be involved in the regulation of Leydig cells (LC) population and function, since nude mice present smaller LC, but with a higher population and higher expression of steroidogenesis-related genes. On the other hand, the catalytic subunit of the DNA double-strand break repair protein (DNA-PKc) seem to have a relevant role on the regulation of Sertoli cells and spermatogenesis, once we observed, in scid mice, a higher number of these somatic cells, followed by a higher daily sperm production, even though they have higher germ cell loss along spermatogenesis, especially in meiosis. Once we observed several testicular alterations in nude mice in sexual maturity, especially regarding LC parameters, in the third paper from this thesis, we investigated, using morphometry, immunohistochemistry and hormone plasmatic levels, the testis function of Foxn1 mutated mice along post-natal development (1 to 25 post-natal days – Pnd) and, in some analysis, also in sexual maturity (70Pnd). In this study, we observed that, in general, the testicular alterations found for nude mice along post-natal development did not follow the same pattern seen in sexual maturity. Furthermore, the results show that Foxn1 seem to affect distinctively the different LC populations and the effect of impaired Foxn1 expression are more significant at late development (from 10Pnd onwards) and at sexual maturity, coinciding with the period when the majority of the LC are the adult type. Foxn1 expression pattern, which increases its frequency and intensity along post-natal development, as well as the double staining of Foxn1 and Hsd17b3, evidence that this transcription factor might be a specific adult LC marker. On the other hand, the identification that some LC express only Foxn1 or Hsd17b3, separately, reinforces the existence of distinct LC populations, according to its protein expression pattern.